RNA-binding protein QKI-5 inhibits the proliferation of clear cell renal cell carcinoma via post-transcriptional stabilization of RASA1 mRNA. Issue 22 (16th November 2016) - Zhang, Rui-Li; Yang, Jun-Ping; Peng, Li-Xia; Zheng, Li-Sheng; Xie, Ping; Wang, Meng-Yao; Cao, Yun; Zhang, Zhi-Ling; Zhou, Fang-Jian; Qian, Chao-Nan; Bao, Yong-Xing
ABSTRACT: Clear cell renal cell carcinoma (ccRCC) is a common pathological subtype of renal cancer. Although the recent application of molecular-targeted agents has modestly improved the prognosis of ccRCC patients, their outcome is still poor. It is therefore important to characterize the molecular and biological mechanisms responsible for the development of ccRCC. Approximately 25% ccRCC patients involves the loss of RNA-binding protein QKI at 6q26, but the role of QKI in ccRCC is unknown. Here, we found that QKI-5 was frequently downregulated in ccRCC patients and its down-regulation was significantly associated with clinical features including T status, M status, and differentiation grade, and poorer patient prognosis. Moreover, QKI-5 inhibited the proliferation of kidney cancer cells both in vitro and in vivo . The subsequent functional studies showed that QKI-5 stabilized RASA1 mRNA via directly binding to the QKI response element region of RASA1, which in turn prevented the activation of the Ras-MAPK signaling pathway, suppressed cellular proliferation and induced cell cycle arrest. Overall, our data demonstrate a suppressive role of QKI in ccRCC tumourigenesis that involves the QKI-mediated post-transcriptional regulation of the Ras-MAPK signaling pathway.